Indirect and Non-use Values of Halda River- A Unique Natural Breeding Ground of Indian Carps in Bangladesh - Kabir, MH; Kibria, MM; Hossain, MM (Journal of Environmental Science and Natural Resources, 2015)
Bangladesh is a Riverine country; however, Halda River is of special interest among them in recent time for being the only tidal freshwater River in the world that serves as a natural spawning ground for major Indian carps. Besides, this River serves some indirect and non-use values. This study aims at estimating the economic worth of the indirect and non-use value of Halda River. Both indirect and non-use values of this River were calculated by using contingent valuation method. The study found that total indirect use value per year from this River was Tk. 29.50 million. We also estimated that total non-use value was Tk. 31.46 million which comprised of bequest value of Tk. 14.85 million and option value of Tk. 16.61 million. The study suggests that this valid source of information should take into consideration for the decision makers in taking projects and programmes aimed at managing this River more wisely in the future. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22092 J. Environ. Sci. & Natural Resources, 6(2): 31-36 2013